Otimização do processo fotocatalítico heterogêneo para o tratamento de percolado de aterro sanitário - de Brito, Núbia Natália; Brota, Giovani Archanjo; Pelegrini, Ronaldo Teixeira; Paterniani, José Euclides Stipp (Eclética Química, 2014)
The conventional methods used in the treatment of this residue lead to a discharge with intense coloration, high organic matter concentration, toxic metals and high toxicity. This work had as objective to study a system integrated for the remediation of the leachate originating from the sanitary landfill of Limeira-SP city The system consisted in a preliminary treatment by a system of slow sand filtration and the subsequent treatment through advanced oxidative processes, considering that the heterogeneous photocatalysis technique with TiO2/UV was experienced in remediation. The photocatalytic treatment was accomplished in a Pyrex glass reactor of approximately 1.7 L (100 mm of internal diameter, 145 mm of external diameter and total height of 300 mm). The experiments were carried out through water refrigeration and internal recirculation system of the leachate. To optimize the treatment process the best methodology it was evaluated to minimize the coloration of the leachate, one of the parameters of larger removal difficulty. The results were satisfactory with leachate coloration reduction in the order of: 66% in 180 min and 76% in 540 min of treatment with the heterogeneous fotocatálise, using 700 mg.L-1 of TiO2, 45°C temperature, 15 L.min-1 air flow and 400 Watts lamp.